Students' problem-solving ability: An analytical practice viewed from the aspect of sociomathematical norm - Rahma Dini, Disya Futhi; Maarif, Samsul (Desimal: Jurnal Matematika, 2022)
This research aims to analyze students’ problem-solving ability in terms of sociomathematical norms. Data was collected using questionnaire sociomathematical norms, ability description tests, and interviews. The total subjects in the research were six students consisting of two students with high sociomathematical norms, two students with moderate sociomathematical norms, and two students with low sociomathematical norms. In this research, there are four indicators, namely understanding the problem, planning the problem, solving the problem, and re-examining the answer. The results showed that subjects who had high sociomathematical norms were able to solve questions on all indicators. Subjects with moderate sociomathematical norms are able to solve problems on the indicators of understanding, planning, and solving problems, but there are errors in the indicators of re-examining. Subjects who have low sociomathematical norms are able to solve problems on the indicators of understanding and planning problems but there are errors in the indicators of solving problems and re-examining.